Usability and functionality factors of the social network site application users from the perspective of uses and gratification theory - Korhan, Orhan; Ersoy, Metin (Springer, 2015)
Uses and gratifications theory (U&G) is a media use paradigm from mass communications research that guides the assessment of consumer motivation for media usage and access. Recent adaptations of U&G research to the internet are incomplete and Internet specific gratifications, and have not identified new Inter-net specific gratifications. The development of social networking sites (SNS) is one of the key phrases when next generation of Internet is concerned. The purpose of this research is to present an analytical framework for explaining uses and gratification for SNS applications. Therefore, this paper investigates in detail how and why people use SNS applications, and what factors make SNS applications particularly appealing, through uses and gratifications perspectives. Our findings show that most of the usability and functionality factors are positively correlated. Except for the Skype application, all usability and functionality factors were identified to contribute significantly to select the SNS application. WhatsApp (total weighted average = 4.13/5.0) is the application which dominates the other applications from the usability and functionality perspectives. Even though Facebook in the most downloaded and mostly used application, our findings provides that the performance of the application in terms of usability and functionality is not satisfactory. This study also showed that, younger and older generations have different taste of SNS application use and different preference for the functionality and usability factors.
Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI (with DOI: 10.1007/s11135-015-0236-7) and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: SNS; Usability and functionality; Uses and gratification; Mobile applications